2017
DOI: 10.24167/celt.v17i1.1139
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Teaching Strategies in Indonesian EFL Writing Classrooms

Abstract: This qualitative study explores motivational teaching strategies employed in English as a foreign language (EFL) writing classrooms and designs a sample of lesson plans elaborating the strategies that were reflected from open-ended questionnaires of sixty-five first-year students at English Language Education Program in a private university in Indonesia. The data analysis reveals possible motivational strategies that are classified into Dornyei's (2001) framework of motivational teaching practice. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
3
3
0
Order By: Relevance
“…They still do awkward structure and unorganized paragraphs. It is in accordance with Mali [6], Aunurrahman [7], and Sitorus & Sipayung [8] who reported that students still have low writing skills if they do not have enough knowledge of vocabulary, the organization of ideas, the grammar, and the mechanics. The mistakes made by the students in writing show that they still need to get serious attention, because these errors interfere with the success of the writing learning.…”
Section: Issn: 2252-8822 supporting
confidence: 86%
“…They still do awkward structure and unorganized paragraphs. It is in accordance with Mali [6], Aunurrahman [7], and Sitorus & Sipayung [8] who reported that students still have low writing skills if they do not have enough knowledge of vocabulary, the organization of ideas, the grammar, and the mechanics. The mistakes made by the students in writing show that they still need to get serious attention, because these errors interfere with the success of the writing learning.…”
Section: Issn: 2252-8822 supporting
confidence: 86%
“…Due to these activities, the teacher feels easy to promote students' self-confidence and self-efficacy to accomplish their learning assignments inside and outside classes. It is in line with some previous studies reporting that students' partnership and teachers' participation can improve students' self-efficacy and motivation (Burić & Kim, 2020;Cave et al, 2018;and Mali, 2017).…”
Section: Skills Of Interpreting and Relatingsupporting
confidence: 91%
“…Furthermore, the students' speaking skill still have difficulties and low confident to speak English in front of the class. It is in line with some studies that informed the same challenges and difficulties (Mali, 2017;Firdaud & Amaniarsih, 2018;Haryadi & Aprianoto, 2020;Suadiyatno et al, 2020;and Salim et al, 2020) Teaching speaking is not an easy job for teachers at the level of senior high schools. Speaking is categorized as a productive skill.…”
Section: Introductionsupporting
confidence: 82%